Protagonismo feminino no cinema de ficção científica : um estudo a partir da personagem Ellen Ripley - Waschburger, Carina Schroder (2020)
This dissertation has as its objective the analysis of the character Ellen Ripley, protagonist of the science fiction film Alien (Ridley Scott, 1979), verifying the possible rupture caused by the character in the North American blockbuster, big budget cinema, especially inside the genre of science fiction. Through a bibliographic survey we were able to understand more deeply the origins of science fiction and how the female characters in the genre were represented until the moment of Ripley's appearance. Based on a criterion for selecting the corpus of films that have narrative and production similarities to Alien, we analyzed the characters Dr. Ellie Arroway from Contact (Robert Zemeckis, 1997), Dr. Ryan Stone from Gravity (Alfonso Cuarón, 2013), Aurora Lane from Passengers (Morten Tyldum, 2016), Dr. Louise Banks from Arrival (Denis Villeneuve, 2016) and Lena from Annihilation (Alex Garland, 2018), in search of characteristics that showed influence from Ridley Scott’s character, Ripley, such as their interpersonal relations, wardrobe, hair, makeup, strength, perception of the journey and character profile. Through the creation of a Character Gallery, we carried out a feminist reading of these characters, using authors such as Barbara Creed (2007), Maureen Murdock (1999) and Laura Mulvey (1975) as the basis. Through this Gallery, we draw parallels between Ripley and the five characters mentioned, allowing us to visualize that there is an influence of Ripley on the characters portrayed here, although a late one. This female protagonism that we are finding in big budget science fiction cinema, is still not very diverse, especially when we consider that there is little recognition and opportunities for filmmakers in roles behind the cameras.